Management of the Uncommon Bladder Cancers: A Single-Center Experience over 10 Years - Youssef Kadouri; Salim Lachkar; Hamza Dergamoun; Hachem El Sayegh; Lounis Benslimane; Yassine Nouini (Advances in Urology)
Background. Under the name of uncommon bladder cancers are gathered rare histological entities which represent less than 5% of bladder tumors. There is not a clear and consensual therapeutic management for these entities. Purpose. To review a single-institution 10-year experience with rare form of bladder cancers detailing the diagnosis, treatment, and patient outcome. Materials and Methods. We performed a retrospective review of 27 medical records of rare bladder cancer form treated at our center between February 2006 and February 2015. The clinicopathologic features are reported with emphasis on treatment and survival. Results. Mean patient age was 65.5 ± 20 yr and 70% of patients were males. Smoking background was found in 16 cases, chronic bladder irritation factors were found in 12 cases, and past urinary tract infection was found in 11 cases. The main symptom was total hematuria (93%) causing an anemia in 16 cases. The two mean histological forms were epidermoid carcinoma (37%) and adenocarcinoma (22%). 26% of patients were found to have extended invasive tumors (T4) at diagnosis. Metastatic disease was confirmed in 8 cases. Our patients were managed by a wide range of therapeutic modalities as total cystectomy with bilateral lymph node dissection (63%), palliative chemotherapy (30%), or concomitant radiochemotherapy (7%). 55.6% of patients were alive one year after diagnosis. Epidermoid carcinoma has the best prognosis followed by leiomyosarcoma and sarcomatoid carcinoma. Neuroendocrine carcinoma has the worst outcome. The overall 5-year survival rate is 33.3%. Conclusion. The rarity and small size of these tumors justify the absence of clear and consensual therapeutic management. No role of total cystectomy concerning the conclusions could be drawn but elements suggest this may be the treatment of choice. The highly aggressive nature of those lesions justifies an aggressive and fast therapy when feasible which gives the best outcomes.